DESAFIOS E PERSPECTIVAS DA PESQUISA ETNOGRÁFICA EM UMA COMUNIDADE QUILOMBOLA | Challenges and perspectives associated with ethnographic research in a Quilombola Commnity (Trabalho & Educação, 2016)
This article considers the recent dynamics of the Quilombola movement in Minas Gerais and particularly the way in which the leaders of the Federation of Quilombola Communities in Minas Gerais (N’Golo) have continued to fight for access to the differentiated rights recognized by the Federal Constitution. Based on these considerations, this article was devised to extant studies on the formation of these political leaders as legal subjects. Consequently, a Master’s in Education project was developed, and this study represents the partial results of it. The study seeks to understand the contributions made by the Quilombola movement to the educational process of these subjects, taking as a reference point the narratives produced by these subjects. The contextual locus is the Quilombola community of Carrapatos of Tabatinga, situated in the central-western region of Minas Gerais. Through fieldwork, an attempt has been made to understand the formative processes present in the community from an ethnographic perspective. Further, this study describes the methodological procedures implemented, analyzes the obstacles encountered as well as the attitudes adopted by the researcher with respect to the research subjects, and describes the complex relationship between subjectivity and objectivity that this involvement in the concerned field causes during the research process. ___Tendo por referência a dinâmica recente do movimento quilombola em Minas Gerais, mais particularmente o acompanhamento de lideranças ligadas à Federação das Comunidades Quilombolas de Minas Gerais (N’Golo), na luta pelo acesso aos direitos diferenciados reconhecidos pela Constituição Federal, elaborou-se a proposta de pesquisa visando a aprofundar os estudos referentes à formação dessas lideranças políticas como sujeitos de direito. Com esse intuito, desenvolve-se o projeto de Mestrado em Educação, do qual esse artigo apresenta-se como resultado parcial. A pesquisa visa compreender as contribuições do movimento quilombola para o processo educativo desses sujeitos, tendo por referência narrativas elaboradas por eles. A investigação tem como locus a comunidade quilombola de Carrapatos da Tabatinga, localizada no centro-oeste mineiro. A partir da inserção no campo, busca-se compreender processos formativos presentes na comunidade sob a perspectiva da etnografia. O artigo descreve os procedimentos metodológicos implementados e analisa os embaraços e as atitudes assumidas pela pesquisadora em sua relação com os sujeitos da pesquisa, bem como a complexa relação subjetividade x objetividade que essa imersão em campo suscita no processo de pesquisa.